Significant Enrichment and Diversity of the Staphylococcal Arginine Catabolic Mobile Element ACME in Staphylococcus epidermidis Isolates From Subgingival Peri-implantitis Sites and Periodontal Pockets - O’Connor, Aoife M.; McManus, Brenda A.; Kinnevey, Peter M.; Brennan, Gráinne I.; Fleming, Tanya E.; Cashin, Phillipa J.; O’Sullivan, Michael; Polyzois, Ioannis; Coleman, David C. (Frontiers in Microbiology, 2018)
Staphylococcus aureus and Staphylococcus epidermidis are frequent commensals of the nares and skin and are considered transient oral residents. Reports on their prevalence in the oral cavity, periodontal pockets and subgingivally around infected oral implants are conflicting, largely due to methodological limitations. The prevalence of these species in the oral cavities, periodontal pockets and subgingival sites of orally healthy individuals with/without implants and in patients with periodontal disease or infected implants (peri-implantitis) was investigated using selective chromogenic agar and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. Staphylococcus epidermidis was predominant in all participant groups investigated. Its prevalence was significantly higher (P=0.0189) in periodontal pockets (30%) than subgingival sites of healthy individuals (7.8%), and in subgingival peri-implantitis sites (51.7%) versus subgingival sites around non-infected implants (16.1%) (P=0.0057). In contrast, S. aureus was recovered from subgingival sites of 0-12.9% of the participant groups, but not from periodontal pockets. The arginine catabolic mobile element (ACME), thought to enhance colonization and survival of S. aureus, was detected in 100/179 S. epidermidis and 0/83 S. aureus isolates screened using multiplex PCR and DNA microarray profiling. Five distinct ACME types, including the recently described types IV and V (I; 14, II; 60, III; 10, IV; 15, V; 1) were identified. ACME-positive S. epidermidis were significantly (P=0.0369) more prevalent in subgingival peri-implantitis sites (37.9%) than subgingival sites around non-infected implants (12.9%) and also in periodontal pockets (25%) compared to subgingival sites of healthy individuals (4.7%) (P=0.0167). To investigate the genetic diversity of ACME, 35 isolates, representative of patient groups, sample sites and ACME types underwent whole genome sequencing from which multilocus sequence types (STs) were identified. Sequencing data permitted ACME types II and IV to be subdivided into subtypes IIa-c and IVa-b, respectively, based on distinct flanking direct repeat sequences. Distinct ACME types were commonly associated with specific STs, rather than health/disease states or recovery sites, suggesting that ACME types/subtypes originated amongst specific S. epidermidis lineages. Ninety of the ACME-positive isolates encoded the ACME-arc operon, which likely contributes to oral S. epidermidis survival in the nutrient poor, semi-anaerobic, acidic and inflammatory conditions present in periodontal disease and peri-implantitis.